THE DEVELOPMENT OF SELF-CONFIDENCE THROUGH BUDDHIST-INTEGRATED GUIDANCE ACTIVITIES ON PERSONAL AND SOCIAL ASPECTS FOR PALI STUDENTS AT WAT KHIAN KHET IN PATHUM THANI PROVINCE - Mantaviro (Kerdsitong), PhramahaMontri; Aphipanyo , PhrapaladSoravit; Mererk, Sayyud; Phrarajsutaporn (Prasak Changsang); Phrasitthisinghasenee (Sophon Singhasenee); PhrakruVichitpatumrat (Kreangkrai Panyateepo) (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed 1) to develop a set of integrated personal and social Buddhist guidance activities to promote self-confidence of Pali students and 2) to study the effect of developing self-confidence with a set of integrated personal and social Buddhist guidance activities of Pali students at the Religious Studies Office, Wat Khian Khet, Pathum Thani Province. This research was a quasi-experimental research using 12 Pali students (monks) with low self-confidence as a sample. The sample group was selected using a self-confidence questionnaire. The research instruments were 1) a questionnaire and 2) a set of integrated Buddhist guidance activities. Data were analyzed using basic statistics, including mean, standard deviation, and statistical tests. The research results found that 1) the process of developing the activity set was effective, focusing on connecting the principles of Dhamma with the daily life of Pali students through various activities such as group discussions, practice exercises, storytelling, and the use of video media to stimulate learning and participation. The process was also reviewed by experts to ensure that it was appropriate for the content, format, and development goals. As a result, the activity set was able to promote the potential and self-confidence of Pali students in both personal and social aspects. 2) The results of developing self-confidence with the integrated Buddhist guidance activity set in personal and social aspects of Pali students found that after using the integrated Buddhist guidance activity set, Pali students had significantly increased self-confidence at a statistical level of 0.05, especially in terms of courage to face the truth and creativity, which were significantly improved. This showed that the activities connecting to the principles of Dhamma with daily life could promote various skills of students very well. This integrated Buddhist guidance activity set not only helps develop students’ self-confidence in all aspects, but it was also a guideline that could be applied in other Buddhist educational institutions to systematically and effectively enhance students’ development.